The regulatory role of alternative splicing in inflammatory bowel disease - Zhou, Jianli; Zhang, Qiao; Zhao, Yuzhen; Song, Yuchen; Leng, Yanan; Chen, Moxian; Zhou, Shaoming; Wang, Zhaoxia (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) mainly includes Crohn's disease (CD) and ulcerative colitis (UC), which have a progressive course of chronic relapse and remission and affect a large number of children and adults worldwide. The burden of IBD is on the rise worldwide, and the levels and trends of disease vary greatly in countries and regions. As with most chronic diseases, the costs of IBD are high, including hospitalizations, outpatient and emergency visits, surgeries, and pharmacotherapies. However, there is no radical treatment for it, and its therapeutic target still needs to be further studied. Currently, the pathogenesis of IBD is still unclear. It is generally believed that the occurrence and development of IBD are related to the environment, gut microbiota, immune imbalance and genetic susceptibility. Alternative splicing contributes to a variety of diseases, such as spinal muscular atrophy (SMA), liver diseases and cancers. In the past, it has been reported that alternative splicing events, splicing factors and splicing mutations are associated with IBD, but there is still no report of splicing related to practical application for the clinical diagnosis and treatment of IBD. Therefore, this article reviews the research progress of alternative splicing, splicing factors and splicing mutations associated with IBD.